Factores de riesgo asociados a caries de infancia temprana en niños, revisión narrativa (2020)
Early childhood caries is a multifactorial disease that is present in children up to 71 months of age. It presents as a rapid and destructive process that affects the stage of temporary dentition. Objective: Describe the risk factors associated with early childhood caries in children 2 to 5 years of age through a narrative review. Materials and Methods: A narrative review based on scientific bibliography was carried out taking into account 45 indexed articles from different years and authors. Articles that were adapted to the topic and its variables were compiled. The results were obtained from the articles studied, and the discussion of the most relevant articles. Results: It was found that 37.5% of the children were free of caries. 47% never brushed their teeth, 43% brushed their teeth only once a day, 10% brushed their teeth 2 or more times a day. As associated risk factors, exclusive prolonged breastfeeding, bottle feeding, sugary foods and drinks, parents' socioeconomic level and educational level, vitamin D deficiency, Candida albicans and type of delivery were found. 80% of caregivers and parents have insufficient knowledge about the oral care that should be given to children. Conclusions: The prevalence of early childhood caries in most of the cases studied was 60%. The associated risk factors are related to exclusive breastfeeding, bottle-feeding, drinks and foods with high sugar consumption, the socioeconomic and educational level of the parents. The lack of knowledge on the part of parents and caregivers influences considerably the appearance of this problem.